2020
DOI: 10.23917/indigenous.v5i2.11086
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing employee’s quality of life during COVID-19 pandemic

Abstract: One result of the COVID-19 pandemic for the wider community, especially employees, is the need to carry out physical distancing in the form of work from home. This phenomenon certainly has consequences on the quality of life felt by employees. The purpose of this study was to determine whether the quality of life of employees who work from home is influenced by variables such as type D personality, anxiety, technology overload, and work-life balance. Participants in this study were 486 employees living in Jaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Inconsistent with these findings, Almalki et al (2012) reported that primary health care nurses were dissatisfied with their current work life, and the major influencing factors were related to inconsistent working hours, shortage of facilities for nurses, inability to balance work with family commitments, lack of vacation time, lack of time with their families, poor staffing and management and supervision practices, poor security and lack of patient care supplies and equipment and recreation facilities. In Indonesia (Mulyani et al, 2020), findings indicate that both internal and external factors could have a different effect on the QOL of employees who were working from home during the pandemic, although the author emphasized that a work‐life balance and technology overload had a positive effect on employees' QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent with these findings, Almalki et al (2012) reported that primary health care nurses were dissatisfied with their current work life, and the major influencing factors were related to inconsistent working hours, shortage of facilities for nurses, inability to balance work with family commitments, lack of vacation time, lack of time with their families, poor staffing and management and supervision practices, poor security and lack of patient care supplies and equipment and recreation facilities. In Indonesia (Mulyani et al, 2020), findings indicate that both internal and external factors could have a different effect on the QOL of employees who were working from home during the pandemic, although the author emphasized that a work‐life balance and technology overload had a positive effect on employees' QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Another analysis of this research shows that work-life balance is a major predictor of employee longevity as it shows higher factor loading on EL. This indicates that if the employee can manage work-life balance through clear verbal expressions, his job satisfaction also increases, positively affecting employee longevity 16,23,35, 46 . Similarly, with job satisfaction, We can conclude that Employee Psychological detachment somewhat mediates the association between Overwork culture and Employee Longevity, even though our hypothesis could not reject the null hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…This paper is a literature review. Recent studies on WFH's effect on work-life balance and deviant behavior has not yet placed spirituality as a moderating variable [6][7][8][9][10][11][12][13][14][15][16][17]. Moderating variables that are often used are age, gender education, organization tenure, and number of children living at Home [2].…”
Section: Introductionmentioning
confidence: 99%